2006
DOI: 10.1177/1744259106064356
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Moisture Diffusivity using the Time Domain Reflectometry (TDR) Method

Abstract: The time domain reflectometry (TDR) method is commonly used for the measurement of moisture content in soil science. In this study, the method is employed for the measurement of moisture profiles in building materials. The practical applications of the method are presented on an example of water penetration into cellular concrete (aerated autoclaved concrete) samples. The measured results are then used for the determination of moisture diffusivity as a function of moisture content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Duration of the suction experiment was 30, 60, and 90 minutes. For the determination of moisture diffusivity, an inverse analysis of experimentally measured moisture profiles was used [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Duration of the suction experiment was 30, 60, and 90 minutes. For the determination of moisture diffusivity, an inverse analysis of experimentally measured moisture profiles was used [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Cataldo et al embedded linear sensing probes in the wall and found that linear sensors based on time domain reflectometry can be applied to the monitoring of moisture in building structures [17]. Pavlík et al applied the time domain reflectometry technique to the moisture distribution measurement of aerated concrete and determined the water diffusion coefficient of the samples based on the measured moisture content [18].…”
Section: State Of the Artmentioning
confidence: 99%
“…There can be applied so called semi-scale experiments that are usually done at laboratory and fragment of the building structure is exposed to the simulated harmful climatic conditions. Since these experiments maintain their laboratory character, precise laboratory methods for measurement of field variables as moisture [4], relative humidity, temperature, deformation and mechanical stresses can be applied. Also the expenses of performed tests can be kept considerably lower compared to a real test house and in-situ measurement [5].…”
Section: Introductionmentioning
confidence: 99%